Pendampingan Pengembangan Usaha Bagi Pelaku Usaha Mikro Kecil dan Menengah “Baso Aci Cingcay Radja Rasa” di Kecamatan Rancaekek - Dadan Hamdani (E-Coops-Day, 2023)
Managers of Micro, Small, and Medium Enterprises (MSMEs) are one of the parties that play a role in advancing the community's economy, but there are still some deficiencies or they do not understand business management. Therefore, community service through the implementation of business development and assistance for business actors "Baso Aci Cingcay Radja Rasa" in Rancaekek is to increase understanding and discussion between resource persons and business actors. The output of business development and assistance for MSMEs is the addition of insight into business knowledge and discussion regarding the follow-up of further business development, namely that the business will grow rapidly in the long term.